Protectionism or Free Trade? Dilemma of Regional Integration and the Difference between Peoples and Countries. A Critique to Miller and Elwood - Monzón, Gabriel Anibal (European Scientific Journal, ESJ, 2017)
Regional integration has always been an area of contention within economic schools. From classical and neoclassical schools (in some areas, they are called liberal and neoliberal), it was argued that integration can be established only in a free trade area. Based on the article by Miller and Elwood, called Protectionism or Free Trade?, they felt the position of the classical school. In this work, I analyzed their arguments and posed a setback concerning their reasons. Regional integration needs, in my opinion, economic protectionism to be able to develop. Based on this statement, I turned to some dogmas of the classical and neoclassical schools to prove it.